Endogenous Working Hours, Overlapping Generations, and Balanced Neoclassical Growth - Andreas Irmen (CESifo GmbH, 2024)
A balanced growth path that accounts for a decline in hours worked per worker approximates the evolution of today's industrialized countries since 1870. This stylized fact is explained in an OLG-model featuring two-period lived individuals equipped with per-period utility functions of the generalized log-log type proposed by Boppart and Krusell (2020) and a neoclassical production sector. Technological progress drives real wages up and expands the amount of consumption goods. The value of leisure increases, and the supply of hours worked declines. Technological progress moves a poor economy out of a regime with low wages and an inelastic supply of hours worked into a regime with high wages and a declining supply of hours worked. The balanced growth path is unique and stable. In the high wage regime, the equilibrium difference equation is available in closed form. A balanced growth path with declining hours worked may also be obtained with endogenous technological progress as in Romer (1986).
Keywords: D15; J22; O33; O41; 330; technological change; comparative economic development; endogenous labor supply; neoclassical endogenous growth; OLG-model